Democracy, equal citizenship, and education. (March 2016) - Callan, Eamonn
Two appealing principles of educational distribution – equality and sufficiency – are comparatively assessed. The initial point of comparison is the distribution of civic educational goods. One reason to favor equality in educational distribution rather than sufficiency is the elimination of undeserved positional advantage in access to labor markets. But civic educational aims of the kind that sustain equal citizenship do not have positional value. Furthermore, such aims intersect with those that augment labor market competitiveness. That seems to pose a dilemma: within the intersection of aims, we have moral grounds to eliminate unfair positional advantage in access to labor markets but also reason to forgo such efforts as repugnant to the civic goods that education properly confers. The dilemma is escaped if positional inequality is not addressed through equalization of educational opportunity but by pursuing what Lesley Jacobs calls 'stakes fairness' in the distribution of social goods that are now too tightly tied to competitive success in labor markets.